Use of life tables to predict the impact of introducing exotic parasitoids, against the cabbage seedpod weevil in North America. Issue 10 (3rd October 2019) - Gillespie, David R.; Broadbent, A. Bruce; Mason, Peter G.; Haye, Tim; Clarke, Peggy; Goettel, Mark S.; Leung, Benjamin
ABSTRACT: Cabbage seedpod weevil, Ceutorhynchus obstrictus (Coleoptera: Curculionidae), is an invasive alien species that impacts seed production of canola, Brassica napus and B. rapa (Brassicaceae), one of Canada's major agricultural crops. To determine the need for and potential impact of introduction of one or more natural enemies for biological control it is essential to understand the mortality factors associated with C. obstrictus both in the native range and in the introduced range. Life tables were constructed for Ontario and British Columbia populations to determine the mortality factors affecting C. obstrictus . These were compared with life tables generated in Switzerland, the area of origin of the weevil. Results indicated that introduction of an exotic specialist parasitoid into canola growing regions of Canada would substantially reduce C. obstrictus populations. This study is the first to compare life tables of an invasive pest in the areas of origin and introduction.